2010
DOI: 10.5120/291-455
|View full text |Cite
|
Sign up to set email alerts
|

Multiresolution Feature Based Subspace Analysis for Fingerprint Recognition

Abstract: The image intensity surface in an ideal fingerprint image contains a limited range of spatial frequencies, and mutually distinct textures differ significantly in their dominant frequencies. This paper presents a multiresolution feature based subspace technique for fingerprint recognition. The technique computes the core point of fingerprint and crops the image to predefined size. The multiresolution features of aligned fingerprint are computed using 2-D discrete wavelet transform. LL component in wavelet decom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
(9 reference statements)
0
2
0
1
Order By: Relevance
“…The percentage values of TSR and EER of proposed method is compared with existing methods presented by Chaven et al [9], George et al [17], Jadhav and Ajmera [21] and Roja and Sawarkar [35]. It is observed that the value of TSR is high in the case of proposed method compared to existing methods (Table 6).…”
Section: Performance Comparison Of Proposed Technique With Existing Techniquesmentioning
confidence: 87%
“…The percentage values of TSR and EER of proposed method is compared with existing methods presented by Chaven et al [9], George et al [17], Jadhav and Ajmera [21] and Roja and Sawarkar [35]. It is observed that the value of TSR is high in the case of proposed method compared to existing methods (Table 6).…”
Section: Performance Comparison Of Proposed Technique With Existing Techniquesmentioning
confidence: 87%
“…The DWT [38] provides spatial and frequency characteristics of an image. It has an advantage over Fourier transform in terms of temporal resolution where it captures both frequency and location information.…”
Section: Dwt Algorithmmentioning
confidence: 99%
“…Parmak izi tanıma ile ilgili diğer yapılan çalışmalar incelendiğinde [11,27,28] özellik çıkarma yöntemi olarak GDD'nin parmak izi sınıflandırmasında yeterli bir yöntem olduğu tespit edilmiştir. GDD'nin en büyük avantajı görüntünün frekans bilgisinin yanında uzaysal bilgisinin de elde edilebilmesi ve frekans verisi bölgeselleştirilip işlemlerin bu bölge ile gerçekleştirilebilir olmasıdır.…”
Section: A Gabor Dalgacık Dönüşümüunclassified